1995
DOI: 10.1007/bf00011470
|View full text |Cite
|
Sign up to set email alerts
|

Root water uptake by kiwifruit vines following partial wetting of the root zone

Abstract: Rates of sap flow and root-water uptake by two 7-year old kiwifruit vines (Acinidia deliciosa) were studied in an orchard with the aim of determining the ability of the vines to alter their spatial pattern of root-water uptake following differential wetting of the root zone. Time-domain reflectometry (TDR) was used to monitor changes in the soil's volumetric water content, 0. The heat-pulse technique was used to monitor sap flow not only in the stem but also in several large roots to see how root flow responde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
76
1
5

Year Published

1996
1996
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(92 citation statements)
references
References 23 publications
10
76
1
5
Order By: Relevance
“…There were also isolated locations within the vertical cross-section where water extraction occurred at a faster rate than that of the surrounding soil. Similar water extraction behavoiur was reported by Green & Clothier ( 1995) for kiwifruit. They attributed this to the vines ability to preferentially extract nearsurface water, and water in the root zone that was more freely available.…”
Section: Patterns Of Water Extractionsupporting
confidence: 85%
See 2 more Smart Citations
“…There were also isolated locations within the vertical cross-section where water extraction occurred at a faster rate than that of the surrounding soil. Similar water extraction behavoiur was reported by Green & Clothier ( 1995) for kiwifruit. They attributed this to the vines ability to preferentially extract nearsurface water, and water in the root zone that was more freely available.…”
Section: Patterns Of Water Extractionsupporting
confidence: 85%
“…Snow (1987) and Green & Clothier (1995) studied the pattern of water extraction for kiwifruit vines in the Manawatu, and Rahardjo (1989) studied the water extraction pattern of apple trees in Hawkes Bay. Such studies provide data on the depth and volume of soil which is supplying all or most of the plants' water requirements, as well as giving an indication of the quantity of water being extracted by the plant.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Nnyamah and Black (1977) claimed that the water extraction pattern of a crop was similar to the distribution of thin roots when the soil water was not limiting. However, Green and Clothier (1995) studied water extraction of kiwifruit vines and observed that root water uptake was more dependent on soil water availability than of thin roots distribution. Yet, there are other studies indicating that the diameter of lateral roots was also a highly variable factor in the soil (Yorke and Sagar, 1970;Cahn et al, 1989;Varney et al, 1993;Jordan et al, 1993;Thaler and Pagès, 1996).…”
Section: Recommendations For Sensor Positioning Within the Effective mentioning
confidence: 99%
“…Eissenstat 1991;Klepper 1991;Green and Clothier 1995). Herbaceous plants are also likely to evolve their root systems into subsoil layers (e.g.…”
Section: Introductionmentioning
confidence: 99%